Government Policy and Financing Options for Solar Energy: World Prospects - Ahmed, Adel; Tyurina, Yuliya G.; Smailova, Zhanara P.; Kurilova, Anastasia A.; Shulus, Aleksei A. (International Journal of Energy Economics and Policy, 2019)
The project financing of solar projects has been proven challenging given the relatively high costs (both for utility solar and rooftop solar) of solar projects, the uncertain life cycle for solar panels, and the lack of business models for financing in the private sector. Several governments have loan-financing programs available for solar-enerprojects. The article describes the peculiarities of government policy in the solar energy field of countries that have already implemented large-scale projects for the construction of SPS (USA, China, India, EU) and countries that have just started to implement this option as an alternative energy into the country’s overall energy system (Eastern Europe: Russia, Kazakhstan). This article is universal in nature. The data obtained and developments can be applied both in the local and international practice of managing an energy business operating in the field of alternative energy - the “solar” industry. Keywords: solar energy; government policy in the solar energy field; alternative energy business. JEL Classifications: 013; Q4; Q42. DOI: https://doi.org/10.32479/ijeep.8212